Study on Community Involvement in Supervision of Social Assistance Programs in Sumpur Kudus District, Sijunjung Regency - Vamella, Djatchzila; Eriyanti, Fitri (Jurusan Ilmu Administrasi Negara, 2025)
AbstractThis study aims to examine community involvement in the oversight of social assistance programs in Sumpur Kudus District, Sijunjung Regency. The primary focus of the study is to understand the forms of community participation, the factors influencing it, the obstacles encountered, and the efforts made to improve the effectiveness of participatory oversight. The research method used was qualitative, with data collection techniques through interviews, observation, and documentation. The results indicate that the level of community involvement remains relatively low and tends to be symbolic, with active participation primarily carried out by community leaders and village officials. Key inhibiting factors include limited access to information, fear of expressing criticism, low social literacy, and the absence of an effective complaint mechanism. Meanwhile, supporting factors for participation include the open leadership of the village head, the role of community leaders, and the use of social media. The village government has undertaken various efforts, such as transparency of recipient data, public outreach, and empowerment of local institutions, but has not yet fully overcome existing structural and cultural barriers. This study recommends strengthening community capacity, an integrated complaint system, and the establishment of community-based oversight institutions to create more inclusive, transparent, and accountable social assistance governance. AbstrakPenelitian ini bertujuan untuk mengkaji keterlibatan masyarakat dalam pengawasan program bantuan sosial di Kecamatan Sumpur Kudus, Kabupaten Sijunjung. Fokus utama penelitian adalah untuk memahami bentuk-bentuk partisipasi masyarakat, faktor-faktor yang mempengaruhinya, kendala yang dihadapi, serta upaya yang dilakukan guna meningkatkan efektivitas pengawasan partisipatif. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa tingkat keterlibatan masyarakat masih tergolong rendah dan cenderung bersifat simbolis, dengan partisipasi aktif lebih banyak dilakukan oleh tokoh masyarakat dan perangkat nagari. Faktor penghambat utama meliputi minimnya akses informasi, ketakutan untuk menyampaikan kritik, rendahnya literasi sosial, dan ketiadaan mekanisme pengaduan yang efektif. Sementara itu, faktor pendukung partisipasi antara lain kepemimpinan wali nagari yang terbuka, peran tokoh masyarakat, dan pemanfaatan media sosial. Pemerintah nagari telah melakukan berbagai upaya seperti transparansi data penerima, sosialisasi publik, serta pemberdayaan lembaga lokal, namun belum sepenuhnya mampu mengatasi hambatan struktural dan kultural yang ada. Penelitian ini merekomendasikan perlunya penguatan kapasitas masyarakat, sistem pengaduan yang terintegrasi, serta pembentukan lembaga pengawasan berbasis komunitas guna menciptakan tata kelola bantuan sosial yang lebih inklusif, transparan, dan akuntabel.